A Educação Física e a formação de professores: pluralidades, projetos pedagógicos, sociedade brasileira e intervenção formativa democrática - (:unkn) unknown (Universidade Federal de Goiás, 2021)
In view of the Brazilian population diversity, it is becoming increasingly urgent to carry out studies and pedagogical practices related to social plurality and, consequently, the understanding of Brazilian society. Physical Education and the problem of the difficulties of teacher training processes, given the Brazilian multiplicity, come up against the attempt to propose school classes / interventions that respect and observe school audiences. In this combination of elements, we seek to debate the possibilities and difficulties in teacher training on Afro-Brazilian and indigenous history in the face of the demands of Law 10.639 / 03 as well as 11.645 / 08 that regulate the mandatory theme “Afro-Brazilian History and Culture Brazilian and Indigenous ”in basic education and to understand elements of this complex relational dynamic. We present a study that investigated several Pedagogical Projects of Physical Education Courses in their textual / formal discourse, with Physical Education courses from the Federal University of Goiás- Regional Catalão (RC / UFG) the starting point. In addition to observing the adequacy to the legislation, we tried to problematize the process of training Physical Education teachers at national level, looking for the way in which cultural diversity, the presence of different groups of Brazilians were thought / not in the training process of the Physical Education teacher. And finally, we report a pedagogical experience with Maculelê that shows us in the practical field how the articulation of ethnic-racial issues, training in the area and Physical Education classes at school works.
Physical Education and teacher training: pluralities, pedagogical projects, brazilian society and democratic formative intervention
Keywords: Formação de professor(a); Educação física; Étnico-raciais; Teacher education; Physical education; Ethnic-racial; CIENCIAS HUMANAS::HISTORIA